THE EFFECT OF STRETCHING LOWER EXTREMITY AND CORE STABILITY ON THE DYNAMIC BALANCE OF UMS BASKETBALL PLAYER: A CASE STUDY - Ramadhani, Suci Indah; Wahyuni, W; Wijianto, W (Universitas Muhammadiyah Surakarta, 2021)
Introduction : The components of physical condition are speed, strength, endurance, flexibility, strength, coordination, balance, and agility in improving the performance of basketball players. one is that the relationship between the ability to balance and the risk of sports injury has been determined in most cases, but the relationship between ability and balance between athletics is less clear. The importance of balance for basketball players itself reduces injuries and improves performance during the game. Case Presentation : Respondents with criteria aged 19-22 years, male and female, work as basketball players. With balance problems who want to follow an exercise program that will be given to improve dynamic balance abilities. Management and outcomes : The patient underwent a treatment consisting of stretching and core stability. Before exercise, patients are asked to perform stretching and core stability independently under the supervision of a physiotherapist. The instrument used is the Y balance test. The results of the paired sample t-test show the mean in pair 1 is 2.35824 with a significant value of 0.000 where p < 0.05 then Ha is accepted and pair 2 is 1.67059 with a significant value of 0.005 where p < 0 0.05 then Ha is accepted, it can be concluded that the lower extremity stretch and core stability affect increasing dynamic balance Discussion : The subjects in this study have dynamic balance disorders because the importance of balance for basketball players can reduce injuries and improve performance during matches. Stretching and core stability can increase flexibility and activate core muscles in athletes to improve balance. Conclusion : Supporting lower severity stretches and core stability can improve the dynamic balance of basketball players.